Contribuição ao arcabouço geológico do sistema aquífero urucuia - Kiang, Chang Hung [UNESP]; de Paula e Silva, Flavio [UNESP] (My University, 2015)
The Urucuia Aquifer System, composed by rocks of Urucuia Group, is distributed over 125,000 km2in the northcentral region of Sanfranciscana Basin, Brazil, and it represents important source of water for public supply and crop irrigation, as well as base flow contribution to São Francisco and Tocantins watersheds. Analysis and correlation of sedimentary successions based on geophysical facies obtained from well logs showed that Urucuia Group covers unconformably sandy sediments of possibly eolian origin in excess of 250 meters in thickness in the central portion of the basin, and changing to clayey sandstones interbedded with shale toward the eastern border of the basin. The study shows that clayey sandstone/shale succession passing to predominantly sandy deposits represents continental sedimentation under increasing aridity conditions, which prevail from the end of the Permian to Triassic, represented by Motuca and Sambaiba formations of Parnaiba Basin. The inclusion of this succession in Urucuia Group led many researchers to consider thicknesses of Urucuia Aquifer System greater than 600 meters, when in reality the maximum aquifer thickness is of approximately 350 meters.
Contribution to the geological framework of the Urucuia Aquifer System